The Effect of Reciprocal Teaching Strategy to Improve Students’ Reading Comprehension at Eleventh Grade of SMA 14 Kabupaten Tangerang in Academic Years 2018/2019 - Leni Ruslaeni; Tenia Ramalia (Foremost Journal, 2020)
ABSTRACT This research aim to help students comprehend English reading texts and make students more practice in learning, especially in discussion. This research use Quantitative Research. Population in this research is 258 students of eleventh grade in SMAN 14 Kab.Tangerang. In selecting the sample, the researcher uses Purposive Sampling Technique. The sample in this research is two classes, experimental class 30 students and controlled class 34 students. There are two variables, first, variable X is Reciprocal Teaching Strategy, and Y is Reading Comprehension. The researcher used T-test to analyse the result. The result of the statistical calculation and hypothesis testing in chapter IV it shows that tcount was higher than the ttable (6,732 > 1,670) which means that Ha is accepted. It means that reciprocal teaching have a significantly positive effect on the English reading comprehension. Keywords : reading comprehension, reciprocal teaching, conventional teaching